Development of Academic Achievement using Cooperative Learning with STAD Method in the Course of Administrative Law for Public Administration - Hanpichai, Suriya (Asia Pacific Journal of Religions and Cultures, 2019)
The purposes of this research are (1) to develop academic achievement using cooperative learning with STAD method and (2) to study student satisfaction using cooperative learning with STAD method in the course of administrative law for public administration. 68 students in the public administration major, who study administrative law in the second semester of the academic year 2017, were selected as samples by using purposive sampling. The researcher conducted the research using a collaborative learning plan with STAD method, then collected the academic achievement test and the student satisfaction questionnaire. The statistics used in the research were frequency, percentage, mean, standard deviation, and T-test. The study indicated that The students’ development of academic achievement using cooperative learning with STAD method was higher after learning than before learning at the level of .05. The student satisfaction using a collaborative learning with STAD method is at the highest level. When considering each aspect, the most valuable aspect is the learning atmosphere, followed by the benefits, contents, and activities.